Procedural method used for tracking in mathematics at the middle school level - Ratigan, Robert (My University, 1988)
The purpose of this project was to determine whether the selection of ability groups by the use of pretests and posttests was a valid means for grouping students. The degree of success was measured by comparing students raw scores on the pretest with their raw scores on the posttest after the grouping and treatment had been completed. During the first week of the first quarter of 1987, a review and pretest were given to the seventh and eighth grade students. The raw scores obtained from these tests were used to group the students in mathematics for the 1987-88 school year. The Pearson Product Moment Correlation formula produced a positive coefficient of .286 when comparing the pretest and posttest. This indicated a low correlation, a definite but small relationship. Based on these findings, the null hypothesis was rejected at the .01 level of confidence.
Keywords: Mathematics -- Study and teaching (Secondary); Ability grouping in education